Seroprevalence of Neospora caninum in cattle in a livestock fair in the Araucania region, Chile - Tuemmers, Christian (2017)
The aim of the study was to determine the seroprevalence of neosporosis in cattle in a livestock fair in the Region of La Araucanía, Chile. Blood samples were collected in 437 cows and heifers belonging to nearby farms. Serum samples were analyzed by the indirect ELISA technique to detect antibodies against Neospora caninum. The results showed that 21.1% of the animals were positive to neosporosis, while 13.9% (61/437) was uncertain and 65.0% (284/437) was negative. The results indicate that the infection is spread in the farms of the region.